Penguatan Branding Produk Dangke sebagai Produk Unggulan Kabupaten Enrekang - Rahmat Riwayat Abadi; Andi Mustika Amin; Syahir Fadli; Ridfan Rifadly Abadi; Kartika Septiary Musa (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
Dangke is a local food product with high nutritional value that has become an inseparable part of the culture and economy of the community. It is made from traditional cheese typical of Enrekang Regency. Despite having great potential as a superior regional product, Dangke micro, small, and medium enterprises (MSMEs) face various obstacles, especially regarding short product durability (expiration date), simple packaging, lack of product innovation, and less than optimal marketing reach. Therefore, strengthening branding and optimizing marketing is crucial to increasing the competitiveness and desirability of Dangke MSMEs. This community service aims to analyze existing conditions, formulate, and implement strategies to strengthen Dangke product branding. The implementation methods include initial surveys, SWOT analysis training, comprehensive training and education on branding (brand identity, visual design), as well as implementation assistance and evaluation of travel impacts. Participatory and community-based approaches are at the heart of this activity. The results of the community service are expected to increase Dangke brand awareness, encourage innovation of derivative products (for example, dangke crackers with innovative flavors and packaging), expand distribution channels (including digital marketing), and ultimately increase sales and income of Dangke MSMEs. This program also has the potential to strengthen the local economy, preserve cultural heritage, and become a model for developing traditional food products in other areas.